Proceedings of the 2016 Conference of the North American Chapter of the Association for Computational Linguistics: Human Langua 2016
DOI: 10.18653/v1/n16-1161
|View full text |Cite
|
Sign up to set email alerts
|

Polyglot Neural Language Models: A Case Study in Cross-Lingual Phonetic Representation Learning

Abstract: We introduce polyglot language models, recurrent neural network models trained to predict symbol sequences in many different languages using shared representations of symbols and conditioning on typological information about the language to be predicted. We apply these to the problem of modeling phone sequences-a domain in which universal symbol inventories and cross-linguistically shared feature representations are a natural fit. Intrinsic evaluation on held-out perplexity, qualitative analysis of the learned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(58 citation statements)
references
References 34 publications
0
58
0
Order By: Relevance
“…Joint Training Approach Another approach to multilingual CWRs is to train a single LM on multiple languages (Tsvetkov et al, 2016;Ragni et al, 2016;Östling and Tiedemann, 2017). We train a single bidirectional LM with charater CNNs and two-layer LSTMs on multiple languages (Rosita, Mulcaire et al, 2019).…”
Section: Multilingual Cwrsmentioning
confidence: 99%
“…Joint Training Approach Another approach to multilingual CWRs is to train a single LM on multiple languages (Tsvetkov et al, 2016;Ragni et al, 2016;Östling and Tiedemann, 2017). We train a single bidirectional LM with charater CNNs and two-layer LSTMs on multiple languages (Rosita, Mulcaire et al, 2019).…”
Section: Multilingual Cwrsmentioning
confidence: 99%
“…Our hypothesis is that, although each language is unique, different languages manifest similar characteristics (e.g., morphological, lexical, syntactic) which can be exploited by training a single model with data from multiple languages (Ammar, 2016). Previous work has shown this to be true to some degree in the context of syntactic dependency parsing , semantic role labeling (Mulcaire et al, 2018), named entity recognition (Xie et al, 2018), and language modeling for phonetic sequences (Tsvetkov et al, 2016) and for speech recognition (Ragni et al, 2016). Recently, de Lhoneux et al (2018) showed that parameter sharing between languages can improve performance in dependency parsing, but the effect is variable, depending on the language pair and the parameter sharing strategy.…”
Section: Introductionmentioning
confidence: 95%
“…This is due to the fact that in order for multilingual parameter sharing to be successful in this setting, the neural network needs to use the language embeddings to encode features of the languages. Previous work has explored this type of representation learning in various tasks, such as NMT (Malaviya et al, 2017), language modelling (Tsvetkov et al, 2016;Östling and Tiedemann, 2017), and tasks representing morphological, phonological, and syntactic linguistic levels (Bjerva and Augenstein, 2018a).…”
Section: Distributional Language Embeddingsmentioning
confidence: 99%